On the additive manufacturing, post-tensioning and testing of bi-material tensegrity structures. (1st November 2015) - Amendola, A.; Hernández-Nava, E.; Goodall, R.; Todd, I.; Skelton, R.E.; Fraternali, F.
Abstract: An investigation on the additive manufacturing and the experimental testing of 3D models of tensegrity prisms and columns is presented. An Electron Beam Melting facility (Arcam EBM S12) is employed to 3D print structures composed of tensegrity prisms endowed with rigid bases and temporary supports, which are made out of the titanium alloy Ti6Al4V. The temporary supports are removed after the additive manufacturing phase, when Spectra cross-strings are added to the 3D printed models, and a suitable state of internal prestress is applied to the structure. The experimental part of the study shows that the examined structures feature stiffening-type elastic response under large or moderately large axial strains induced by compressive loading. Such a geometrically nonlinear behavior confirms previous theoretical results available in the literature, and paves the way to the use of tensegrity prisms and columns as innovative mechanical metamaterials and smart devices.